Qualitative Comparison of Cultured Skin Microbiota From the Inguinal Region of Obese and Nonobese Patients Eligible for Hip Arthroplasty - Philip Mark Anderson, MD; Thiemo Frank; Michaela Herz, MD; Oliver Kurzai, MD; Maximilian Rudert, MD; Tizian Heinz, MD; Thiên-Trí Lâm, MD (Arthroplasty Today)
Background: With the rising prevalence of obesity, surgeons are frequently confronted with the problem of treating osteoarthritis of the hip via arthroplasty (total hip arthroplasty) in severely obese patients. To reduce the surgical impact, minimal-invasive approaches are often chosen. For this reason, the direct anterior approach has gained popularity but is suspected of leading to more wound complications in obese patients, especially by Gram-negative pathogens. Causative differences of the skin microbiome have been suspected but not yet proven. Methods: Patients scheduled for total hip arthroplasty via direct anterior approach were screened for inclusion. The study group was defined as patients with a body mass index ≥35 and an abdominal pannus hanging over the incision site, whereas nonobese patients served as the control group. Samples of the microbiome were taken 2-3 cm distal and lateral to the superior anterior iliac spine using plates and swabs. Species identification was carried out by mass spectrometric analysis. Results: The study group consisted of 28 patients, the control group of 36 patients. The most frequent potential pathogen on the skin was Staphylococcus epidermidis in both the groups. Microbiota found in obese patients showed significantly higher prevalence of Gram-negative bacteria from the order Enterobacterales. Wound complications were more frequent in the study group, but this was not statistically significant. Conclusions: Obese patients with abdominal pannus present higher rates of colonization with Enterobacterales at the incision site of the direct anterior approach. Modifications of the antibiotic regime and the incision should be considered in this special patient population.